Pengembangan Bahan Ajar Berbasis Multimedia Interaktif Adobe Flash di Kelas IV Sekolah Dasar - Lisa Syupriyanti; Desyandri Desyandri (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The purpose of this research is to develop the teach material of multimedia interactive adobe flash in 4th grade elementary school. The research is development and research that uses ADDIE models made up of analyze, design, development, implementation and evaluation. Research data is obtained from tests of validity, practicality, and effectiveness. Validating results are seen in terms of validation of content, language, and graph is 86,63% in highly valid categories. The results of the practice can be seen from the teacher’s response is 92,33% and the learner’s response is 90,6%. While the effective results can be seen from learners activities are 90,3 and the learning from the knowledge aspect is 84, the attitude aspect is 90 and the skill aspect is 91. The conclusion of the research is that the multimedia interactive adobe flash taught material developed for 4th grade elementary school is declared valid, practical and effective.